m-Learning - die neue Welle? Mobiles Lernen für Deutsch als Fremdsprache. - Mitschian, Haymo (Kassel University Press, 2010)
Two phenomena are characteristic for the current developments in the information and communication technology (ICT): the devices to access and use digital content improve in terms of usability and performance, and the digital content itself expands fastly. On this developments and the changes in usage patterns start the reflections in the present volume on mobile learning centering on the question how foreign-language learning can benefit from these new usage-patterns and technologies.